2013
DOI: 10.1186/1471-2261-13-97
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the occurrence of acute coronary syndrome: results of the Malaysian National Cardiovascular Disease (NCVD) Database Registry (March 2006 - February 2010)

Abstract: BackgroundThe National Cardiovascular Disease (NCVD) Database Registry represents one of the first prospective, multi-center registries to treat and prevent coronary artery disease (CAD) in Malaysia. Since ethnicity is an important consideration in the occurrence of acute coronary syndrome (ACS) globally, therefore, we aimed to identify the role of ethnicity in the occurrence of ACS among high-risk groups in the Malaysian population.MethodsThe NCVD involves more than 15 Ministry of Health (MOH) hospitals natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 81 publications
(105 reference statements)
3
34
1
Order By: Relevance
“…In our study, the Malaysian Chinese population showed the lowest frequency of the 1082G allele (2%), which is consistent with a previous report in the Chinese populations of Singapore, China, and Taiwan (Trejaut et al, 2004). Genetic variation between ethnic groups may explain the ethnic differences in specific disease prevalence and disease profiles (Wang et al, 1997;Hee et al, 2008;Bhoo-Pathy et al, 2012;Lu and Nordin, 2013). In Malaysia, for instance, systemic lupus erythematosus is most prevalent amongst the Chinese ethnic group compared to Malays and Indians (Hee et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the Malaysian Chinese population showed the lowest frequency of the 1082G allele (2%), which is consistent with a previous report in the Chinese populations of Singapore, China, and Taiwan (Trejaut et al, 2004). Genetic variation between ethnic groups may explain the ethnic differences in specific disease prevalence and disease profiles (Wang et al, 1997;Hee et al, 2008;Bhoo-Pathy et al, 2012;Lu and Nordin, 2013). In Malaysia, for instance, systemic lupus erythematosus is most prevalent amongst the Chinese ethnic group compared to Malays and Indians (Hee et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…In Malaysia, ACS appears to manifest at a younger age with more severe comorbidity, more severe disease, and higher rates of obesity and diabetes [50,78,79]. Even within Malaysia, risk factor profiles differ with ethnicity: NCVD ACS registry data show Malay patients have higher rates of obesity, Chinese patients have the highest rates of hypertension and dyslipidemia, and Indian patients have the highest rate of diabetes [80].…”
Section: Risk Factorsmentioning
confidence: 98%
“…4 Most patients (85%) belonged to middle socioeconomic status, and 9% and 6% were from lower and upper socioeconomic status respectively (Table 3). In CREATE study most (52.5%) patients were from lower-middle socioeconomic status.…”
Section: Discussionmentioning
confidence: 98%